2023
DOI: 10.1002/biof.2020
|View full text |Cite
|
Sign up to set email alerts
|

Investigating rutin as a potential transforming growth factor‐β type I receptor antagonist for the inhibition of bleomycin‐induced lung fibrosis

Wisurumuni Arachchilage Hasitha Maduranga Karunarathne,
Kyoung Tae Lee,
Yung Hyun Choi
et al.

Abstract: Idiopathic pulmonary fibrosis (IPF) is a chronic lung condition characterized by the abnormal regulation of extracellular matrix (ECM) and epithelial‐mesenchymal transition (EMT). In this study, we investigated the potential of rutin, a natural flavonoid, in attenuating transforming growth factor‐β (TGF‐β)‐induced ECM regulation and EMT through the inhibition of the TGF‐β type I receptor (TβRI)‐mediated suppressor of mothers against decapentaplegic (SMAD) signaling pathway. We found that non‐toxic concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“… Yang et al (2019) reported that wedelolactone reversed the increase of bleomycin-induced fibrosis markers collagen-1 and α-SMA, and the decrease of anti-fibrosis markers E-cadherin, and it significantly prevented the phosphorylation of TGF-β1 and Smad2/3. Karunarathne et al (2023) found that rutin attenuated the gene expression of fibronectin, elastin, collagen-1, and TGF-β, as well as myoblast differentiation from MRC-5 lung fibroblast cells accompanied by the downregulation of α-SMA.…”
Section: Discussionmentioning
confidence: 92%
“… Yang et al (2019) reported that wedelolactone reversed the increase of bleomycin-induced fibrosis markers collagen-1 and α-SMA, and the decrease of anti-fibrosis markers E-cadherin, and it significantly prevented the phosphorylation of TGF-β1 and Smad2/3. Karunarathne et al (2023) found that rutin attenuated the gene expression of fibronectin, elastin, collagen-1, and TGF-β, as well as myoblast differentiation from MRC-5 lung fibroblast cells accompanied by the downregulation of α-SMA.…”
Section: Discussionmentioning
confidence: 92%
“…Sesamin, isolated from Sesami Nigrum Semen , protected against the airway fibrosis induced by ovalbumin via reducing the activation of myofibroblast and the accumulation of collagen via modulating the TGF-β1/Smad3 pathway [ 51 ]. Rutin, another major compound of QZJFD and MQZJFD ameliorated the lung fibrosis induced by BLM in mice through suppressing the TGF-β1/α-SMA/Col I and III pathway [ 52 , 53 ]. Glycyrrhizic acid was also reported to alleviate BLM-induced pulmonary fibrosis in mice and rats [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%